Trivial Injuries In A Rural Area Of Ambala - Singh A.J; Kaur A (Wolters Kluwer Medknow Publications, 1993)
Research question: What are the management practices of a rural community towards trivial injuries sustained by them. Objectives: To study 1. action taken by individuals in the management of trivial injuries, 2.factors related with trivial injuries. Design: Cross sectional study. Setting: Rural area of Haryana. Participants: individuals attending the outpatient department of Community Health Centres, Primary Health Centres, sub-centres, local registered medical practitioners (RMPs). Study variables: Trivial injuries. Outcome Variables: Management- home based or hospitals based. Results: Peripheral parts of the extremities- hands, finger, feet and toes were most commonly affected by trivial injuries. A variety of local applications like tobacco, salt, kerosene, oil, nail polish, turmeric, urine, were used for initial wound care. Conclusion: Rural people of Haryana use a variety of local applications, some not very hygienic, for the immediate management of injuries. Education is required to make them aware of hygienic practices where would care is concerned.